MANAJEMEN ZAKAT BERBASIS SISTEM INFORMASI PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KOTA BAUBAU - Sabirin, Abdul Rasyid; Selfiana, Wa Ode (JURNAL INFORMATIKA, 2019)
The National Zakat Amil Agency (BAZNAS) is an official body formed by the Government based on RI Decree No. 8 of 2001 which has the duty and function to collect and distribute zakat, infaq, and almsgiving at the national level. Constraints from the presentation of information related to zakat management on BAZNAS in Baubau City still use Microsoft Office applications so that the resulting data is not well integrated. This research aims to design and make an application for the Zakat Management Information System at the Baubau City National Amil Zakat Agency (BAZNAS) to facilitate the management of zakat data on Baznas so as to manage data. The method of data collection used is observation and interviews with parties related to this study. This study resulted in the application of Zakat Management Information Systems at the Baubau City National Zakat Agency (BAZNAS) which facilitated the management process of zakat data processing, consists of data collection of zakat providers, zakat recipients, zakat distribution and zakat income reports so that data is stored properly and easily managed.Keywords: baznas, infaq, management, almsgiving, zakat.